Effects of physical exercise on metabolic syndrome in psychotic disorders: A systematic review with meta-analysis of randomized controlled trials - Arantxa Ancín-Osés; Mikel Izquierdo; Manuel J. Cuesta; Mikel L. Sáez de Asteasu (European Psychiatry, 2025)
Abstract Background Physical exercise improves mental and physical health of individuals with severe mental illness (SMI); however, its impact on metabolic syndrome remains unclear.